Y2O3:Ho3+ and ZnO:Bi3+: a selection for enhancing color quality and luminous flux of WLEDs - Nguyen Thi Phuong Loan; Nguyen Doan Quoc Anh (Institute of Advanced Engineering and Science, 2020)
As the luminescence industry develops, the white light light-emitting diode (LED) package with a single chip and a single phosphor although produces good luminous flux but has a poor color rendering index (CRI) can no longer fulfill the requirements of modern lighting applications. Therefore, this research is conducted to response to the urgent demands of improving other lighting qualities of WLED while maintaining high luminous efficiency. To achieve this target, we applied the new WLED package, which contains multi-chips and multi-phosphor layers, and have obtained outstanding results in both CRI and luminous efficacy. Two types of phosphor used in the WLED package are Y2O3:Ho3+ and ZnO:Bi3+. A color configuration model is also developed to adjust the shading of the white-light LED module. The results of this research show that the triple-layer phosphorhas the best performance when applied in a white-light LED package, which is demonstrated through better color quality, CRI and luminous efficacy, The manufacturers can rely on this research to produce the optimal-quality WLED, or WLED that is appropriate to their quality demands.